EFFECTIVENESS OF PHYSICAL THERAPY AS PRIMARY TREATMENT FOR NECK PAIN AND CERVICAL RADICULOPATHY: CLINICAL CHARACTERISTICS OF PATIENTS WITH SYMPTOM RECURRENCE - SRIRAM K; JYOTI S. JEEVANNAVAR; SANTOSH JEEVANNAVAR (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: Existing literature substantiates non-operative management, particularly physical therapy, and adjunctive modalities, as the primary approach for treating cervical radiculopathy (CR). However, there is a subset of patients who do not improve with primary physical therapy, hence requiring additional procedures. This study evaluates the short-term efficacy of physical therapy interventions in individuals diagnosed with CR and describing the clinical characteristics of patients who experienced symptom recurrence during follow-up. Methods: In this prospective cohort study of 60 patients (18–60 years) diagnosed with CR by a medical practitioner and fulfilling inclusion criteria were evaluated using tests and scales for pain, disability, quality of life, strength, and dexterity. Individualized physical-therapy protocols were designed with evaluations at admission, discharge and up to 6 months. Patients’ improvements were documented, and the clinical characteristics of patients with symptom recurrence were described. Results: The mean numerical pain rating scale, neck disability index and CR impact scale scores at entry and discharge were (6.9±1.4 and 1.1±1.1), (25.1±7.1 and 3.7±3.3) and (48.6±21.3 and 84.7±8.2), respectively. The scores were significantly different with a Z-score of −6.7359. At p<0.0001, t-Score −21.146 at p<0.0001 and t-Score 12.86 at p<0.0001, the Grip strength was lower on the affected side (50.5±12.8 vs. 59.9±14.2, p<0.0001). 10 participants reported improved quality of life, and all the patients reported excellent relief from symptoms, which was consistent at 3 and 6-month follow-ups. During continued clinical follow-up beyond the study period, eight patients reported recurrence of symptoms. Conclusion: The results from our study support physical therapy intervention as the primary treatment modality for neck pain and CR. There is a certain subset of patients in whom the results worsen over time who end up requiring additional procedures, including surgery. Six of the eight patients who experienced symptom recurrence were subsequently diagnosed with early-stage cervical myelopathy, indicating that for a subset of patients initially diagnosed with radiculopathy, the underlying pathology may be more complex and involve the spinal cord. This highlights the importance of vigilant monitoring for myelopathic signs during follow-up to facilitate timely surgical referral.